A inclusão de egressos do sistema prisional adotada como causa e os consumidores: o caso Ben & Jerry´s - Cunha, Daniel Fasanella Brito da (2021)
Within a few years, Brazil will have the largest prison population in the world. This world title is, of course, uncomfortable in several respects and is a consequence of a policy of mass incarceration that reduces detention centers to a stock of unwanted people that society should forget that they exist. But, at some point, the sentences are served and the inmates have their freedom, and it is from this that an individual, previously invisible, needs to reintegrate into society, the first step being to enter the labor market. On the other hand, there is a movement of companies that have been deepening their work with cause marketing, adopting an activist posture, focused on society, and finding in the new dynamics of the relationship between consumers and brands, in addition to mediatization, an environment, most of the time, favorable. Of these, a portion that adopts the inclusion of minorities as a cause, such as Ben & Jerry's, seeks, in working with these causes, a connection point with their consumers in an attempt to combine positive impact and benefit for their brand and their business. This work aims to identify how consumers are involved in the work of causes and activism of the company B&J, whose framework explored concepts of cause marketing, activism and recent events studied from the perspective of social representations theory. In addition to collecting information and an exploratory interview with the company's executive, two phases of research were applied, including a survey method, with 96 respondents, and interviews with 10 consumers of the brand. The relevance of this study lies in the identification of consumer profiles and their consumption behavior with the brand, as well as their involvement and identification with the work of inclusion of ex-prisoners that is carried out. Additionally, in the results, a dialogue with companies that already act in this way or intend to assume an activist posture is proposed, something that is, according to the research findings, extremely expected by consumers.